Characterisation of titanium dioxide-single walled carbon nanotubes composite fibres prepared by the wet spinning technique - Dechakiatkrai C. (2014)
Carbon nanotubes (CNTs) have been extensively interested due to their unique mechanical and electrical properties. Owning to their outstanding electronic, thermal, structural properties, chemical stability, low density, high mechanical strength, large surface area, high modulus and high conductivity, CNTs are desired for a broad range of applications in many fields such as energy storage, molecular electronics, nanoprobes, sensors, composite materials and templates. To enhance the performance of titanium dioxide (TiO2) nanotubes for future applications, single-walled carbon nanotubes (SWNTs) were chosen for making the composite material with TiO 2. In this work, a simple, rapid and effective wet spinning methodology has been conducted and successfully applied to fabricate the TiO2 composites fibres. The TiO2 nanorods were dispersed with SWNTs using biopolymer as a dispersant. By employing the wet spinning technique and choosing an appropriate coagulant, the stable suspension of TiO2 and TiO2 composite were directly injected into the coagulation bath to produce fibres. These fibres were characterized using atomic force microscopy (AFM), scanning electron microscopy (SEM), conductivity measurement, and Raman spectroscopy. Moreover, the AFM results indicated the samples characteristics according to SWNTs at various concentrations in TiO 2 suspension. This study also suggested that different concentration of SWNTs affected the RMS roughness value. The Raman spectra showed peaks which corresponded to their characteristic peaks of TiO2 and SWNTs. The SEM results revealed that the bundles of SWNTs connecting with 2 points of the TiO2 surface was clearly seen whereas some aggregations obtaining from either TiO2 or a dispersant were found. The compounds were identified mainly by comparing their Raman spectra with those of bare TiO 2 and SWNTs. In addition, the combination between CNTs and TiO 2 has been studied to improve the properties of these composite fibres. The mechanical and electrical properties along with surface morphology and electrochemistry of the resulting fibres were also investigated. The presence of SWNTs clearly improved the electrical properties of the composite fibres compared to bare TiO2. The application of the TiO 2/SWNTs composites will be further investigated. © 2008 IEEE.